The Analysis of the Influence of the Network Chinese Culture Communication on College Student Sport Psychology - Liu, Xiangyang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study aims to determine the psychological effects of online Chinese cultural communication on university students. In this study, literature research, mathematical statistics, and other methods were used to investigate and analyze college students' mental health and sports participation awareness, as well as the factors influencing their mental health. Sixty college students were chosen as the research subjects. After establishing a control group and an experimental group, the changes in the psychological stress level of each group's members in response to the intervention of various sports items were studied and analyzed. There were positive changes in the psychological factors of the subjects. Sports intervention in network Chinese culture communication can significantly improve college students' stress-coping ability and psychological tolerance, alleviate their psychological stress, and promote their physical and mental health development. There are some differences between the intervention effects of various sports, but they are not readily apparent. It is recommended that both internal and external physical education measures be taken to create a positive sports environment on campus and improve the psychological health of college students through physical activities.